2016
DOI: 10.22260/isarc2016/0054
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Optimizing Lap Splice Positions within Concrete Elements to Minimize Cutting Waste of Steel Bars

Abstract: One of the material waste streams in the construction of concrete structures is the waste generated during cutting of steel bars to their final required length. The amount of waste generated to produce the required length of steel bars can be affected considerably by the cutting patterns adopted. Waste can, therefore, be minimized by optimizing the cutting pattern to be selected. Cutting patterns are a combination of bar lengths and, thus any change in the required lengths directly affects cutting patterns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 9 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…Yeo and Gabbi showed that the structural optimization of a beam cross section can result in a decrease in the embodied energy of the beam on the order of 10% at the expense of about a 5% increase in the cost relative to a cost-optimized member. The total amount of materials used in a structure, and thus the embodied carbon of the structure, has also been shown to be considerably affected by the amount of waste produced during component manufacturing, on-site construction and installation process [76,77]. Therefore, minimizing the waste generated during production and construction can be considered a potential strategy for minimizing the embodied carbon of structures.…”
Section: Materials Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeo and Gabbi showed that the structural optimization of a beam cross section can result in a decrease in the embodied energy of the beam on the order of 10% at the expense of about a 5% increase in the cost relative to a cost-optimized member. The total amount of materials used in a structure, and thus the embodied carbon of the structure, has also been shown to be considerably affected by the amount of waste produced during component manufacturing, on-site construction and installation process [76,77]. Therefore, minimizing the waste generated during production and construction can be considered a potential strategy for minimizing the embodied carbon of structures.…”
Section: Materials Minimizationmentioning
confidence: 99%
“…Therefore, minimizing the waste generated during production and construction can be considered a potential strategy for minimizing the embodied carbon of structures. Moussavi et al showed through a case study that minimizing the trim loss in cutting reinforcing steel rebars resulted in a decrease of about 7.7% and 49.6% in the total amount of material used and generated waste, respectively [76].…”
Section: Materials Minimizationmentioning
confidence: 99%
“…Rebar cutting waste (RCW) is generally estimated to be 3-5% in the construction planning stage [1][2][3][4]. However, technology to reduce RCW was not developed at the construction field, so more than 5% is generated in the actual construction [5][6][7][8][9]. To solve this problem, many studies was conducted to minimize RCW [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Kwon, K. et al, (2021) stated that the rebars amount used in the world was 947 million tons in 2019, and assuming RCW ratio of 3 to 5%, global RCW of 2841~47.35 million tons are generated annually [17][18][19]. And the study stated that if 0.3416 ton•CO2/ton [20] of CO2 emission from rebar is applied, about 971~16.18 million ton of CO2 emission is calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous studies have been conducted on minimizing cutting wastes, and various optimization algorithms have been proposed. However, in reality, cutting wastes are still generated in the process of cutting and bending of rebars, which are at least 3% to 5% [3][4][5][6][7], and as much as 5% [4,[6][7][8][9][10][11] to 8% [12], compared to the volume shown in the structural drawings.…”
Section: Introductionmentioning
confidence: 99%